2021
DOI: 10.1007/s10596-021-10087-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of flow diagnostics to rank model ensembles

Abstract: Ensembles of geomodels provide an opportunity to investigate a range of parameters and possible operational outcomes for a reservoir. Full-featured dynamic modelling of all ensemble members is often computationally unfeasible, however some form of modelling, allowing us to discriminate between ensemble members based on their flow characteristics, is required. Flow diagnostics (based on a single-phase, steady-state simulation) can provide tools for analysing flow patterns in reservoir models but can be calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…To obtain further dynamic properties for FD that approximate the reservoir behaviour such as well allocation factors, drained or swept reservoir regions, influence regions that are affected by the interaction between wells, or the volume of fluid displaced by the injected fluid as a function of time, it is convenient to compute the steady-state concentration c of an inert and virtual tracer for the reservoir (Lie et al, 2015;Møyner et al, 2015;Rasmussen and Lie, 2014;Watson et al, 2021) v⋅∇c = 0, c| inflow = 1 (4) Shook and Mitchell (2009) demonstrated how other characteristics that approximate the dynamic reservoir behaviour, such as the dynamic Lorenz coefficient, storage efficiency, or breakthrough times, can be calculated from the distribution of τ in the reservoir. Using the storage capacity Φ(τ) and flow capacity F(τ) given by Møyner et al ( 2015)…”
Section: Governing Equations For Flow Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain further dynamic properties for FD that approximate the reservoir behaviour such as well allocation factors, drained or swept reservoir regions, influence regions that are affected by the interaction between wells, or the volume of fluid displaced by the injected fluid as a function of time, it is convenient to compute the steady-state concentration c of an inert and virtual tracer for the reservoir (Lie et al, 2015;Møyner et al, 2015;Rasmussen and Lie, 2014;Watson et al, 2021) v⋅∇c = 0, c| inflow = 1 (4) Shook and Mitchell (2009) demonstrated how other characteristics that approximate the dynamic reservoir behaviour, such as the dynamic Lorenz coefficient, storage efficiency, or breakthrough times, can be calculated from the distribution of τ in the reservoir. Using the storage capacity Φ(τ) and flow capacity F(τ) given by Møyner et al ( 2015)…”
Section: Governing Equations For Flow Diagnosticsmentioning
confidence: 99%
“…these reservoir models in an intuitive and time-effective way (Alshakri et al, 2023;Jackson et al, 2022). The resulting model ensemble can be formally compared using clustering techniques based on specific reservoir performance metrics (Scheidt and Caers, 2009;Watson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this particular example, the entire computations were carried out on a standard desktop PC for the Tarbert and Ness formations; it took only 16 and 23 min to simulate the whole workflow, respectively. Such fast computations allow us to analyse a much wider range of geological scenarios, parameter combinations, and well patterns, and hence enable us to screen and explore a broader range of uncertainties prior to selecting models and scenarios for more detailed full-physics simulations using appropriate clustering and ranking techniques (Caers and Scheidt 2011;Scheidt and Caers 2009;Park et al 2013;Watson et al 2021). Performing similar screening simulations would likely take days using coupled full-physics simulations.…”
Section: Case Study 2: Upper Ness Formationmentioning
confidence: 99%
“…Results from flow diagnostics can therefore be used to select a small subset of reservoir models based on their dynamic performance from a large model ensemble without compromising on the ability to forecast future reservoir performance and estimate the impact of uncertainties (e.g. Caers and Scheidt 2011;Scheidt and Caers 2009;Park et al 2013;Watson et al 2021). Our proposed poro-mechanical integration with flow diagnostics frameworks hence provides us with a computationally efficient estimation of how poro-mechanics might impact reservoir performance, which allows us to compare, contrast, and rank different stress-sensitive reservoir models and select individual scenarios for further detailed studies that use computationally demanding full-physics models that couple geomechanical and hydrodynamical simulations.…”
Section: Introductionmentioning
confidence: 99%